Associations of Prior Chronic Use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and Glucocorticoids With Cachexia Incidence and Survival - Olaechea, Santiago; Gilmore, Anne; Alvarez, Christian; Gannavarapu, Bhavani S.; Infante, Rodney; Iyengar, Puneeth (Frontiers in Oncology, 2022)
Background: Cachexia is an inflammatory and metabolic syndrome of unintentional weight loss through depletion of muscle and adipose tissue. There is limited knowledge of how chronic use of non-steroidal anti-inflammatory drugs (NSAIDs) and glucocorticoids affect cachexia development. The purpose of this study was to investigate associations between prior long-term use of NSAIDs or glucocorticoids with cachexia incidence and post-diagnosis weight loss progression in a retrospective cancer patient cohort. Methods: Of 3,802 lung or gastrointestinal cancer patient records, 3,180 comprised our final cohort. Patient demographic information, tumor qualities, medication histories, and comorbidities were assessed. Cachexia was defined as having developed prior to oncologic treatment. Statistical evaluations included categorical, multivariate logistic regression, and log-rank survival analyses. Development of substantial post-diagnosis weight loss was calculated and interpreted for patients without cachexia at diagnosis. Results: Chronic prior use of any NSAID or glucocorticoid medication was associated with approximate absolute and relative reductions in cachexia incidence at diagnosis of 10 and 25 percent (P<0.0001). In multivariate analyses, NSAID medications demonstrated a 23 percent reduction in cachexia incidence likelihood (OR=0.770; 95% CI=0.594, 0.998; P=0.0481). Patients without cachexia at diagnosis were significantly more likely to develop substantial post-diagnosis weight loss from pre-diagnosis use groups of glucocorticoids (OR= 1.452; 95% CI=1.065, 1.979; P=0.0183) or NSAIDs (OR=1.411; 95% CI=1.082, 1.840; P=0.011). Conclusions: Our findings suggest a protective effect of prior anti-inflammatory medications, primarily NSAIDs, against manifestations of the cachexia phenotype at cancer diagnosis. These observations support further exploration of potential therapeutic benefits from anti-inflammatory medications early in cancer management.